Medroxyprogesterone acetate or long-acting progesterone in the biostimulation of lambs - Monteiro, Claudia Dias [UNESP] (2010)
The aim of this study was to evaluate the response of prepubertal ewe lambs to exogenous administration of either medroxyprogesterone acetate (MAP) or long-acting progesterone (LAP) together with biostimulation. Two Pool Dorset adult males and 75 mixed-breed prepubertal ewe lambs (average of 179 days-old and 30.0 kg) were used. The females were randomly assigned to three different groups. In the first group the females were submitted to the insertion of intravaginal sponges containing MAP (60 mg) for 12 days and were then biostimulated for eight weeks. In the second group the females were submitted to a single injection of LAP (225 mg) and then to biostimulation for eight weeks. In the last group, the females were only submitted to biostimulation for eight weeks. Animals were considered cyclic when plasma progesterone (P4) concentration exceeded 1.0 ng/mL in at least one of two consecutive blood samples taken within a 7-day interval in three distinct experimental moments. After treatments 93.3% of the females disregarding their group started their cyclicity and most of them (92.0%), continued to be cyclic after 63 days of either MAP or LAP together with biostimulation under both male and female effect. We conclude that prepubertal ewe lambs when submitted to protocols of either MAP or LAP followed by biostimulation result in puberty at the 7 month of age. It can be deducted that some ewe lambs submitted to the administration of either MAP or LAP together with biostimulation promoted a multiplier effect upon the other young females that were then stimulated to start cyclicity.